2022
DOI: 10.3847/1538-4357/ac897c
|View full text |Cite
|
Sign up to set email alerts
|

The Lyα Emission in a C1.4 Solar Flare Observed by the Extreme Ultraviolet Imager aboard Solar Orbiter

Abstract: The hydrogen Lyα (H i Lyα) emission during solar flares has rarely been studied in spatially resolved images, and its physical origin has not been fully understood. In this paper, we present novel Lyα images for a C1.4 solar flare (SOL2021-08-20T22:00) from the Extreme Ultraviolet Imager aboard Solar Orbiter, together with multi-wave-band and multiperspective observations from the Solar Terrestrial Relations Observatory Ahead and the Solar Dynamics Observatory spacecraft. It is found that the Lyα emission has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…For all three flares, the peaks in the Lyα emission coincided with the peaks of the HXR emission as measured by RHESSI (dashed vertical lines in Figure 4), suggesting that these impulsive enhancements were driven by nonthermal electron incidence. This is in agreement with a number of previous studies that reported a temporally correlated relationship between Lyα and nonthermal emission (Nusinov et al 2006;da Costa et al 2009;Milligan et al 2017;Dominique et al 2018;Lu et al 2021;Li et al 2022). However, each flare also exhibits a prolonged decay time before returning to background levels.…”
Section: Irradiance Variabilitysupporting
confidence: 93%
“…For all three flares, the peaks in the Lyα emission coincided with the peaks of the HXR emission as measured by RHESSI (dashed vertical lines in Figure 4), suggesting that these impulsive enhancements were driven by nonthermal electron incidence. This is in agreement with a number of previous studies that reported a temporally correlated relationship between Lyα and nonthermal emission (Nusinov et al 2006;da Costa et al 2009;Milligan et al 2017;Dominique et al 2018;Lu et al 2021;Li et al 2022). However, each flare also exhibits a prolonged decay time before returning to background levels.…”
Section: Irradiance Variabilitysupporting
confidence: 93%